2022
DOI: 10.3390/life12101514
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interventions in Rat Models of Preterm Hypoxic Ischemic Injury: Effects of Hypothermia, Caffeine, and the Influence of Sex

Abstract: Infants born prematurely have an increased risk of experiencing brain injury, specifically injury caused by Hypoxia Ischemia (HI). There is no approved treatment for preterm infants, in contrast to term infants that experience Hypoxic Ischemic Encephalopathy (HIE) and can be treated with hypothermia. Given this increased risk and lack of approved treatment, it is imperative to explore and model potential treatments in animal models of preterm injury. Hypothermia is one potential treatment, though cooling to cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 203 publications
0
6
0
Order By: Relevance
“…Previous work has suggested that decreases of 4 ​°C in core body temperature for 5 ​h have detrimental effects on the brain of late-preterm rats after exposure to HI [ 69 ]. In contrast, more moderate reductions in body temperature of 1.5 ​°C for 2 ​h resulted in substantial decreases in brain injury in male and female rats after exposure to HI injury at P7 [ 37 , 70 ]. Consequently, a temperature of 30 ​°C was selected for our subsequent hypothermic studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has suggested that decreases of 4 ​°C in core body temperature for 5 ​h have detrimental effects on the brain of late-preterm rats after exposure to HI [ 69 ]. In contrast, more moderate reductions in body temperature of 1.5 ​°C for 2 ​h resulted in substantial decreases in brain injury in male and female rats after exposure to HI injury at P7 [ 37 , 70 ]. Consequently, a temperature of 30 ​°C was selected for our subsequent hypothermic studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have previously reported differential responses between male and female pups in response to treatment with hIAIPs after exposure to HI [ 23 , 25 , 27 ]. Nonetheless, although differential effects in males and females have been observed in neonatal rats with and without exposure to neuroprotective strategies for HI-related brain injury [ 37 , 70 , 94 , 106 , 114 , 115 ], post-hoc analysis of the whole-body therapeutic National Institute of Child Health and Human Development Neonatal Research Network Induced Hypothermia trial by sex suggests that the outcomes did not differ between the male and female infants [ 116 , 117 ]. Similarly, studies in larger animals including fetal sheep and pigs do not support differential effects by sex like those observed in rodents [ 37 , 70 , 94 , 106 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early treatment correlated with the preterm infant brain and late treatment with the term infant brain. While there is no approved treatment for neuroprotection in preterm infants, Caff has been shown to be neuroprotective (McLeod et al, 2022(McLeod et al, , 2023. Similar to Caff, Ibu has been shown to exhibit neuroprotection in a number of animal models of perinatal brain injury, likely via attenuation of the inflammatory response (Prasad et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For hypothermia, it is thought that caffeine promotes energy preservation and reduces cytotoxic edema, free radicals, inflammation, and apoptotic cell death due to its anti-inflammatory properties. However, since factors like behavioral and neuroprotective outcomes might differ according to sex, this comparison needs to be considered to translate from animal to human [97]. On the other hand, in preterm infants with AOP, phenotypes and the expression of certain receptors have been associated with caffeine treatment and efficacy.…”
Section: Future Directionsmentioning
confidence: 99%